2015
DOI: 10.5897/ajest2014.1853
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of lycopene and vitamin E against diazinon-induced biochemical changes in Oreochromis niloticus

Abstract: The aim of the present study was to evalute the protective role effect of lycopene and vitamin E on oxidative stress in Oreochromis niloticus exposed to diazinon (DZN). Adult fish were exposed to two sublethal concentrations (0.76 and 2.3 mg/l) of DZN against the ameliorative effect of lycopene (10 mg/kg) and vitamin E (50 mg/kg) for 14 and 28 days. DZN significantly led to a decline in total antioxidant capacity (TAO). However, lipid peroxidation (LPO), DNA fragmentation percentage, super oxide dismutase (SOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Two processes that contribute to lycopene’s antioxidative impact are the formation of adducts and allylic hydrogen abstraction [ 107 , 108 ]. The type of the reacting free radical, the structural characteristics of lycopene, and the positioning and direction of lycopene inside the membrane in biological systems are all elements that impact these potential interactions [ 109 , 110 , 111 ].…”
Section: Lycopene As An Antioxidantmentioning
confidence: 99%
“…Two processes that contribute to lycopene’s antioxidative impact are the formation of adducts and allylic hydrogen abstraction [ 107 , 108 ]. The type of the reacting free radical, the structural characteristics of lycopene, and the positioning and direction of lycopene inside the membrane in biological systems are all elements that impact these potential interactions [ 109 , 110 , 111 ].…”
Section: Lycopene As An Antioxidantmentioning
confidence: 99%
“…Through their actions, toxins disrupt homeostasis, alter gene expression, and cancer-related metabolic signalling pathways [ 224 ]. Research has demonstrated that lycopene as a dietary supplement effectively mitigates the deleterious effects of myco-, bacterial, and chemical toxins [ 225 ] [ 125 , 226 , 227 ], fungicides [ 228 ], pesticides [ 229 ], herbicides [ 230 ], and fluoride [ 231 ]. It is hypothesised that lycopene mediates protection against toxins through its potent antioxidant, chelating, and antiapoptotic properties [ 224 ].…”
Section: Lycopene: Protective Effects Against Toxinsmentioning
confidence: 99%